Les communicants : des professionnels de la réputation engagés dans la fabrique de l’agence d’architecture - Margaux Darrieus (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Although promotional communication professionals are hardly visible within the field of architecture, their influence is indisputable. Evolving outside and within the architecture firm, whether as independents or employees, they support architects in building their reputation and that of their company, as they construct images and discourses associated with their name, creating portfolios, websites and monographic books, organizing visits for the editors of specialized reviews, as well as privileged meetings with potential owners. A qualitative investigation seems the only appropriate method to be able to approach these discrete intermediaries, who have been seldom studied. Based on a series of interviews as well as a long-term participant observation experiment within a specialized review team, this article explores the trajectories and practices of these actors who gravitate in great proximity around the architect, building their profiles and their companies’ profiles within the architectural market, facilitating access to contracts and closely approaching the architectural project.